Extensive Transcriptome Changes During Natural Onset and Release of Vegetative Bud Dormancy in Populus - Howe, Glenn T.; Horvath, David P.; Dharmawardhana, Palitha; Priest, Henry D.; Mockler, Todd C.; Strauss, Steven H. (Frontiers in Plant Science, 2015)
To survive winter, many perennial plants become endodormant, a state of suspended growth maintained even in favorable growing environments. To understand vegetative bud endodormancy, we collected paradormant, endodormant, and ecodormant axillary buds from Populus trees growing under natural conditions. Of 44,441 Populus gene models analyzed using NimbleGen microarrays, we found that 1,362 (3.1%) were differentially expressed among the three dormancy states, and another 429 (1.0%) were differentially expressed during only one of the two dormancy transitions (false discovery rate p-value < 0.05). Of all differentially expressed genes, 69% were down-regulated from paradormancy to endodormancy, which was expected given the lower metabolic activity associated with endodormancy. Dormancy transitions were accompanied by changes in multiple genes associated with DNA methylation (via RNA-directed DNA methylation) and histone modifications (via Polycomb Repressive Complex 2), confirming and extending knowledge of chromatin modification as major features of dormancy transitions. Among the chromatin-associated genes, we found two genes similar to SPT (SUPPRESSOR OF TY) that were strongly up-regulated during endodormancy. Transcription factor genes and gene sets that were atypically up-regulated during endodormancy include a gene that seems to encode a trihelix transcription factor and genes associated with proteins involved in responses to ethylene, cold, and other abiotic stresses. These latter transcription factors include ETHYLENE INSENSITIVE 3 (EIN3), ETHYLENE-RESPONSIVE ELEMENT BINDING PROTEIN (EBP), ETHYLENE RESPONSE FACTOR (ERF), ZINC FINGER PROTEIN 10 (ZAT10), ZAT12, and WRKY DNA-binding domain proteins. Analyses of phytohormone-associated genes suggest important changes in responses to ethylene, auxin, and brassinosteroids occur during endodormancy. We found weaker evidence for changes in genes associated with salicylic acid and jasmonic acid, and little evidence for important changes in genes associated with gibberellins, abscisic acid, and cytokinin. We identified 315 upstream sequence motifs associated with eight patterns of gene expression, including novel motifs and motifs previously associated with the circadian clock and responses to photoperiod, cold, dehydration, and ABA. Analogies between the regulation of flowering and endodormancy suggest important roles for genes similar to SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL), DORMANCY ASSOCIATED MADS-BOX (DAM), and SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 (SOC1).